Women, teaching and leadership in 1 Timothy 2:11-15 : a rhetorical-critical study, with reference to Angola - David, Teresa Chateia (Stellenbosch : Stellenbosch University, 2019)
Thesis (MTh)--Stellenbosch University, 2019.